The Spectator, 1972-03-02 - Spectator, Valdosta State University (Valdosta State University, 1972)
The Spectator, March 2, 1972. Vol. 38, Issue 19 -- REBELS TO DEFEND GIAC CROWN IN AMERICUS SATURDAY NIGHT -- India Study Grant Is Awarded To VSC Dept. -- SGA PETITIONS DUE MARCH 8 -- LUCK LEADS REBS TO GIAC PLAYOFF -- SPEECH WORKSHOP TO DRAW HIGH SCHOOLERS
Digitized from original print, Valdosta State University Archives and Special Collections, March 15, 2015.
Keywords: Valdosta State College; Valdosta State University; VSC; VSU; The Spectator; The VSC Spectator; 1970s; 1972; Valdosta State College's Student Newspaper